2000
DOI: 10.1029/2000ja000145
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of the topside ionosphere over Arecibo during the total solar eclipse of February 26, 1998

Abstract: Abstract. The Arecibo incoherent scatter radar facility was operated on February 26, 1998, and was used to observe the total solar eclipse that occurred over the Caribbean. A maximum of 87% obscuration was observed over Arecibo at 1430 LT (1830 UT). The radar was operated using an experimental technique, which uses a 300/•s single/multi-frequency pulse, to gather data from the altitude range 146-2412 km. The Sheffield University plasmasphere ionosphere model was used to interpret the measurements. The electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 37 publications
3
33
0
3
Order By: Relevance
“…The ionospheric response to solar eclipses has been the purpose of many works, both theoretical and experimental. Changes in the ionospheric plasma density and temperature, diffusion processes, etc., have already been studied and time constants estimated (Baron and Hunsuker, 1973;Jakowski et al, 1983;Cohen, 1984;MuellerWodarg et al, 1998;Huang et al, 1999;McPherson et al, 2000; and the references therein). Thus, it is now proven that the plasma redistribution during eclipses may lead to modifications of the electron density profile shape, measurable by the equivalent slab thickness.…”
Section: Introductionmentioning
confidence: 95%
“…The ionospheric response to solar eclipses has been the purpose of many works, both theoretical and experimental. Changes in the ionospheric plasma density and temperature, diffusion processes, etc., have already been studied and time constants estimated (Baron and Hunsuker, 1973;Jakowski et al, 1983;Cohen, 1984;MuellerWodarg et al, 1998;Huang et al, 1999;McPherson et al, 2000; and the references therein). Thus, it is now proven that the plasma redistribution during eclipses may lead to modifications of the electron density profile shape, measurable by the equivalent slab thickness.…”
Section: Introductionmentioning
confidence: 95%
“…They used a technique which allowed them to make separate measurements of the H + and O + temperatures; no such ability exists for the AE data. MacPherson et al [2000] found a drop of around 200 K for the H + temperature and none for the O + temperature. In other words, the temperatures of the heavier ions behave the same as the neutral gas, while the ionized hydrogen temperature responds similarly to electron temperature.…”
Section: Discussionmentioning
confidence: 94%
“…Both experimental [ Salah et al , 1986] and theoretical [ Roble et al , 1986] examinations of the annular eclipse of 30 May 1984 at Millstone Hill found no change in ion or neutral temperatures at this altitude. MacPherson et al [2000] examined the solar eclipse of 26 February 1998 using incoherent scatter radar at Arecibo. They used a technique which allowed them to make separate measurements of the H + and O + temperatures; no such ability exists for the AE data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations